State bureaucracy and the politics of development in Algeria : 1962-1978 - R KABACHE (Revue des Sciences Humaines)
The main aim of this paper is to examine the emergence and development of state bureaucracy which gained control of the means of production and administration after the political independence of Algeria. Administrative control and the control of means of production play a role equivalent to that of the ownership of the means of production.The bureaucrats strengthened their position through the model of development which Algeria had adopted and  which was based on heavy industry which was given priority